Effectiveness of educational intervention on knowledge regarding cervical cancer and its prevention among married women in Chandragiri Municipality, Kathmandu - Shrestha, Bipsana; Paudel, Narayani (Journal of Kathmandu Medical College, 2020)
Background: Cervical cancer is the leading cancer and the leading cause of cancer deaths in women in low and middle-income countries. There is lack of knowledge regarding cervical cancer and its prevention among Nepalese women which leads to inadequate screening. Although cervical cancer is acknowledged as a preventable disease, it is still a major health burden for women in many developing countries because an adequate scale of screening programs is lacking. Objective: To evaluate the effectiveness of educational intervention on knowledge regarding prevention of cervical cancer among married women in Chandragiri Municipality. Methodology: Pre-experimental research design (One-group pretest-posttest design) was used. Through non-probability purposive sampling, 65 married women of Chandragiri municipality, ward no. 04 were included in the study. The final sample size was 62 as three samples were lost during post-test. Structured questionnaire was used for data collection via an interview method. The educational intervention was administered after pretest. Posttest was done with the same instrument two weeks after intervention. Data analysis was done using SPSS version 20. Descriptive statistics and inferential statistics (paired t-test) were used, hypothesis was tested at 5% level of significance. Results: Out of 62 respondents, 54.8% of the respondents had adequate knowledge in the pre-intervention phase and 62.9% had adequate knowledge in the post-intervention phase regarding cervical cancer and its prevention. There was a significant increase in mean score of overall knowledge from 15.82 to 25.75 after educational intervention (p<0.001). Conclusion: Mean knowledge score of the respondents increased significantly after educational intervention indicating that the educational intervention was effective.